Role of Personality Functioning in Predicting Interpersonal and Emotional Problems - Leila Zaeimzadeh; Mozhgan Lotfi; Mahdi Amini (Journal of Mazandaran University of Medical Sciences, 2020)
Background and purpose: Personality functioning impairment (criterion A) is considered as one of the two essential criteria for diagnosing personality disorders in DSM-5. It includes self (identity and self-direction) and interpersonal (empathy and intimacy) components. This study aimed to investigate the role of personality functioning in predicting interpersonal and emotional problems. Materials and methods: A cross-sectional research was conducted in 245 eligible men and women selected by convenience sampling in Tehran, Iran, 2019. Data were collected using a demographic questionnaire, the Level of Personality Functioning Scale (LPFS-BF 2.0), the Inventory of Interpersonal Problems (IIP-32), and the Difficulties in Emotion Regulation Scale (DERS). Data were analyzed applying Pearson correlation coefficient and hierarchical linear regression. Results: Findings showed significant positive correlations between all personality functioning components and interpersonal and emotional problems (P<0.01). Also, hierarchical regression showed that the interpersonal personality functioning (P<0.01) and the subscale of empathy (P<0.01) could significantly predict interpersonal problems. Furthermore, a significant positive relationship was found between interpersonal functioning and emotional problems (P<0.01). In the meantime, the intimacy functioning had a stronger predictive value than empathy (P<0.01). Conclusion: Educational and interventional programs that could improve and adjust communication skills, and enhance empathy and intimacy in personality functioning could be of great help in overcoming interpersonal and emotional problems.